ANALISIS NILAI KARAKTER RELIGIUS DALAM TRADISI UPACARA PANGGIH PADA PERNIKAHAN ADAT JAWA DI DESA SUNGAI MERAH KECAMATAN PELAWAN KABUPATEN SAROLANGUN - Sinta Wahidha; Hendra; Tohap Pandapotan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the religious character values embedded in the panggih ceremony tradition within Javanese customary weddings in Sungai Merah Village, Pelawan Subdistrict, Sarolangun Regency. The panggih ceremony is a central and symbolic procession that reflects deep spiritual and cultural meanings in Javanese wedding rituals. This research uses a descriptive qualitative approach with data collected through observation, interviews, and documentation. The findings reveal that the panggih tradition contains several religious character values, such as gratitude to God, respect for parents, awareness of roles and responsibilities in marriage, and the spirit of mutual cooperation during the ceremony. These values not only strengthen social bonds within the community but also serve as a medium for cultural transmission and moral education in alignment with religious teachings. The study concludes that the panggih ceremony plays a dual role—not only as a cultural practice but also as a vital instrument in shaping religious character among the Javanese community in Sungai Merah Village